IL-6 decodes sex and diet-dependent circadian and metabolic rhythms - Gonzalez-Vila, Antia; Ibrahim-Alasoufi, Ali Mohammad; Luengo-Mateos, Maria; Pardo-Garcia, Victor; Diaz-Lopez, Alejandro; Fernandez-Rodriguez, Belen; Poutanen, Matti; Ohlsson, Claes; Tena-Sempere, Manuel; Dieguez-Gonzalez, Carlos; Garcia-Garcia; Maria del Carmen; et al. (Elsevier BV, 2026)
Objective: Interleukin-6 (IL-6) is a pleiotropic cytokine involved in immune regulation and energy metabolism. Its diurnal secretion influences core circadian components, emphasizing its critical role in circadian biology. Despite known sex differences in immune, circadian, and metabolic processes, how IL-6 integrates these processes remains poorly understood.
Methods: IL6 knockout (KO) and control mice of both sexes were phenotyped for circadian and metabolic traits under standard (STD) and high-fat diet (HFD), fasting, and time-restricted feeding. Molecular analyses in muscle, liver, and hypothalamus assessed clock gene expression and IL-6 signaling pathway. Circulating sex steroid hormones were quantified to examine their contribution to the observed sex-specific phenotypes.
Results: IL-6 deficiency disrupts circadian locomotor and metabolic rhythms in a sex- and diet-dependent manner. Males exhibit impaired light-driven circadian rhythms under STD conditions and metabolic misalignment under HFD, whereas females display greater circadian resilience under STD conditions but increased vulnerability to circadian disruption during HFD. Additionally, IL-6 emerges as a novel regulator of the food-entrainable oscillator (FEO), linking food anticipatory activity and metabolic cycles under both STD and HFD in a sex-dependent manner.
Conclusions: These findings identify IL-6 as a critical mediator of circadian-metabolic plasticity, shaping sex- and diet-specific trade-offs between circadian stability and metabolic homeostasis. Our study highlights IL-6 as a potential therapeutic target for mitigating circadian misalignment-associated metabolic disorders, with implications for the timed modulation of IL-6 signaling.